Human Rights Violation Settlement by Regional Office of Ministry of Law and Human Rights In Maluku Province Through Public Communication Service - Yared Hetharie; Yosia Hetharie (Fakultas Hukum Universitas Pattimura, 2022)
Introduction: Currently, there are many human rights violation allegations in Maluku either done vertically by Government or horizontally by the society. High number of complaints received by the People Communication Service (Yankomas) team in the Regional Office of Ministry of Law in Maluku and Human Rights indicates this phenomenon. Yankomas is tool to settle human rights violation allegation that has its legal ground on the Presidential Regulation Number 75 Year 2015 about National Human Rights Action Plan 2021-2022.Purposes of the Research: The purpose of this study is to examine the procedure for resolving allegations of human rights violations and mapping the handling of cases of alleged human rights violations through the Community Communication Service at the Maluku Kemenkumham Regional Office.Methods of the Research: This study uses empirical legal research methods related to phenomena and facts that occur in the field, especially those faced by members of the Community Communication Service Team of the Moluccas Kemenkumham Regional Office. The approach used is the statutory approach and the case approach.Results of the Research: In the year 2021-2022 complaints that enter the Regional Office of the Ministry of Law and Human Rights Maluku in the form of written complaints and verbal complaints, the number of complaints in this period has increased. The role of Yankomas in resolving allegations of human rights violations satisfies the complainants because all incoming complaints are properly resolved or explained. The settlement is carried out by inviting the reported party and other relevant stakeholders in a coordination meeting in which solutions and solutions are sought for the problems complained of. Public Communication Services should continue to be developed considering the high number of public complaints who are starting to realize that there is a role for the state to protect, promote the enforcement of human rights.